2016
DOI: 10.1016/j.jval.2016.03.1411
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preference for Using Computers, Smartphones, and Internet to Participate in Clinical Trials

Abstract: Objectives: Patient engagement and adherence are critical to the success of clinical trials. Electronic patient-reported outcomes (ePROs) are increasingly used to evaluate clinical trial endpoints. This study characterized how subjects prefer to use various types of technology to report ePROs in a clinical trial. Considering patient preference during trial design may reduce patient burden and improve patient engagement. MethOds: 416 subjects with osteoarthritis (OA, n= 104), type 2 diabetes (n= 102), chronic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, solutions currently available do not take full advantage of the available technology, are not supported by clinical evidence and/or lack clinical validation (Majumder and Deen, 2019). Different studies have shown patients with CORD have interest in and willingness to use information technologies to help in the management of their disease (Fonseca et al, 2006;Khurana et al, 2016;Dumais et al, 2019). In addition, patients' interest in real-time tracking of health status and progress, reminders, positive reinforcement and support have been reported (Simpson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, solutions currently available do not take full advantage of the available technology, are not supported by clinical evidence and/or lack clinical validation (Majumder and Deen, 2019). Different studies have shown patients with CORD have interest in and willingness to use information technologies to help in the management of their disease (Fonseca et al, 2006;Khurana et al, 2016;Dumais et al, 2019). In addition, patients' interest in real-time tracking of health status and progress, reminders, positive reinforcement and support have been reported (Simpson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%